Pemodelan Run Up Tsunami Selat Sunda Menggunakan Smoothed Particle Hydrodynamics (SPH) - Ananda Nur Izza; Desy Nur Fitriani; Thalia Anindya Ardine; Dian Candra Rini Novitasari (Mathematics Department, Faculty of Sciences and Technology Unisda Lamongan, 2025)
The tsunami that occurred in the Sunda Strait in December 2018 caused extensive damage in the coastal areas of Banten and Lampung. This event was triggered by the collapse of Mount Anak Krakatau, which suddenly displaced water masses without being preceded by a tectonic earthquake, so its generation mechanism differs from that of a typical tsunami. In this study, the Smoothed Particle Hydrodynamics (SPH) method was used, utilizing Sunda Strait bathymetry data to construct a simulation domain, while the tsunami source was represented by fluid deformation around Mount Anak Krakatau. This study aimed to model the propagation and run-up of the tsunami to understand the distribution of the resulting wave energy. The simulation results showed that the tsunami waves tended to propagate northeast and southeast, with a high energy concentration towards the coasts of Banten and Lampung. Although limitations in particle resolution and numerical parameters made run-up values ​​less accurate, the SPH method was able to qualitatively describe the fluid dynamics at the wave generation and propagation stages. This approach shows potential as a tool for studying the characteristics of non-tectonic tsunamis and supporting disaster mitigation efforts in coastal areas.